STUDENTS' MENTAL HEALTH IN THE CONTEXT OF GLOBALIZATION: PROBLEMS AND SOLUTIONS (Universal International Scientific Journal, 2026)
In the era of globalization, the issue of students' mental health has become one of the most pressing problems. The rapid development of technology, the influence of social networks, competition in the educational process and moral pressure are increasing mental stress, anxiety and emotional instability in students. This article analyzes the factors affecting the mental health of students in the context of globalization, and proposes effective solutions for their consequences and prevention. Psychological education, the development of emotional intelligence, and the establishment of counseling centers in universities play an important role in strengthening mental health. The results of the study show that mental stability is one of the most important factors in the personal and academic success of students.
Keywords: globalization, student, mental health, stress, adaptation, psychological support, education.